DELAYED PRESENTATION OF PITUITARY TUMOUR WITH HYPOPITUITARISM - Jayaraman, Parvina A/P; Nordin, Hidayatil Alimi Keya; Abdullah, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hypopituitarism is a relatively uncommon disorder in the paediatric population, and its prevalence in children is not yet well established. This condition can be caused by any disease that affects the pituitary gland, stalk or hypothalamus. We describe a patient who presented late with short stature and hypopituitarism. CASE A 16-year-old male presented with short stature and delayed puberty. He denied any headaches or visual problems. He was born full-term with a birth weight of 3.2 kg. Developmental milestones were normal. At presentation, his height was 139 cm and his weight was 35 kg (both below 3rd percentile). Midparental height was 167.5 cm. His Tanner stage was 1 and testicular volume was 2 ml bilaterally. His visual field assessment was unremarkable. Hormonal analysis demonstrated hypopituitarism as validated by the following: LH <0.12 IU/L (1.8-11.8 IU/L) FSH 0.8 IU/L (3.03-8.08 IU/L) fasting morning testosterone 0.32 nmol/l (0.69- 26.16 nmol/l), IGF-1 38.7 ng/ml (226-903 ng/ml), morning serum cortisol 158 nmol/l (102-558 nmol/l) with inappropriately normal ACTH 4.37 pmol/L (1.6-13.9 pmol/L) fT4 7.74 pmol/L (11.4- 17.6) TSH 2.08 m IU/L (0.47-3.41) prolactin 671.28 m IU/L (72.6-407.4). Synacten test revealed inadequate response with peak cortisol 184 nmol/l at 60 minutes. His bone age was delayed between 11 - 13 years. Magnetic resonance imaging of the pituitary gland revealed the presence of an enhancing lesion at the suprasellar region, at the centre of the optic chiasm abutting the proximal part measuring 1.0 x 1.2 x 1.1 cm (AP x W x CC). Differential diagnosis includes craniopharyngioma or pilocytic astrocytoma. He was replaced with glucocorticoid and levothyroxine while awaiting a parental decision regarding tumour excision. CONCLUSION Hypopituitarism can present in neonates, infants, children, and adolescents with multifactorial aetiologies. Timely diagnosis of this condition is crucial for effective intervention and management of affected children. The key to successful management of hypopituitarism lies in a high index of suspicion, coupled with increased awareness and appropriate hormone replacement therapy. Access to facilities for surgical intervention is essential for the survival and good prognosis of affected children.